2019
DOI: 10.3390/ijms20133166
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Trial Using Autologous Ex Vivo Expanded NK Cells and Cytotoxic T Lymphocytes for Cancer Treatment in Vietnam

Abstract: (1) Background: Immune cell therapy recently attracted enormous attention among scientists as a cancer treatment, but, so far, it has been poorly studied and applied in Vietnam. The aim of this study was to assess the safety of autologous immune cell therapy for treating lung, liver, and colon cancers—three prevalent cancers in Vietnam. (2) Method: This was an open-label, single-group clinical trial that included 10 patients with confirmed diagnosis of colon, liver, or lung cancer, conducted between March 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Survival and quality of life were increased in most patients. 26 Besides the number and the purity, another important entity in NK cellenrichment is to yield cytotoxic subset. Considering the conventional classification (based on the expression of CD16 and CD56), CD56 hi CD16 dim regulatory NK cells were observed to be decreased after expansion (25.321 vs. 7.39).…”
Section: Discussionmentioning
confidence: 99%
“…Survival and quality of life were increased in most patients. 26 Besides the number and the purity, another important entity in NK cellenrichment is to yield cytotoxic subset. Considering the conventional classification (based on the expression of CD16 and CD56), CD56 hi CD16 dim regulatory NK cells were observed to be decreased after expansion (25.321 vs. 7.39).…”
Section: Discussionmentioning
confidence: 99%
“…These cells, by their direct contact or in a TCR-dependent manner, attack the target cells and provide a safe harbor to other cells. Interestingly, CTLs could also destroy tumor cells through an MHC-independent manner attacking autologous tumor cells without affecting other cells within the area [96,97]. Cancer immunotherapy using transfer of TCR genes [98,99] or adoptive transfer of CTLs [100,101] has been facing an important problem in harvesting enough antigen-specific CTLs for therapy.…”
Section: Generation Of T Lymphocytes From Ipsc Technology: a New T-cementioning
confidence: 99%
“…al. reported that this therapy (NK Cells and CTLs from Peripheral Blood) is not only safe and possible, but also could increase the quality of life for patients (Liem et al, 2019).…”
Section: Nk Cell Therapy Of Tumormentioning
confidence: 99%
“…al. reported that this therapy (NK Cells and CTLs from Peripheral Blood) is not only safe and possible, but also could increase the quality of life for patients(Liem et al, 2019). T A B L E 3 (Continued) , acute lymphoblastic lymphoma; AML, acute myeloid leukemia; CLL, chronic lymphocyte leukemia; CR, complete response; CRC, colorectal carcinoma; CY, cyclophosphamide; DSRCT, desmoplastic small round cell tumor; EWS, Ewing sarcoma; GVHD, graft versus host disease; MM, multiple myeloma; MRC, metastatic renal carcinoma; N/D, not determined; NSCLC, non-small cell lung carcinoma; PR, partial response; RCC, renal cell carcinoma; RMS, rhabdomyosarcoma; TBI, total body irradiation.…”
mentioning
confidence: 99%